Handbook of clinical anesthesia - Barash, Paul G. (Philadelphia, PA : Lippincott Williams & Wilkins/Wolters Kluwer, 2013)
"The Handbook of Clinical Anesthesia, Seventh Edition, is a companion to the parent textbook, Clinical Anesthesia, Seventh Edition. This widely acclaimed reference parallels the textbook and presents content in a concise outline format with additional appendices. The Handbook makes liberal use of tables, graphics, and clinical pearls, to enhance rapid access of the subject matter. This comprehensive, pocket-sized reference guides you through virtually every aspect of perioperative, intraoperative, and postoperative patient care."--Provided by publisher.
Keywords: Anesthesia -- Handbooks; Anesthetics -- Handbooks